Nieruchomość jako źródło lokalnych dochodów publicznych - Poniatowicz, Marzanna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Real estates create considerable and stable sources of income for the communes in the form of: real property tax, agricultural tax, forest tax, planning charges, adjacent charges, rent charges, leasing charges, perpetual land usufruct charges, perpetual administration charges. Incomes of the communal budgets connected to real estates, can be increased in the way of balanced management of communal territories and effective management of municipial property. Inevitable is also introduction of cadastral tax and adoption of a real estate value as the basis for taxation. The system of allowances and tax relieves also requires thorough verification. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 250-262